Strategi Pemberdayaan Perempuan dalam Menunjang Ekonomi Kreatif dalam Perspektif UKM - Marwan, Jubery; Franky, Franky; Nugroho, Michael Adhi; Utama, Zahera Mega; Rasdan, Rathoyo; Rahayu, Rahayu (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2026)
This Community Service Program aims to formulate a women's empowerment strategy to support the creative economy based on small and micro enterprises in urban areas. Through a participatory and contextual approach, this activity was carried out in Pondok Labu Village, South Jakarta, involving women micro-entrepreneurs as active partners. The implementation methodology included identifying community needs, designing training modules, conducting training and mentoring, and evaluating the activity's outcomes qualitatively and quantitatively. The results indicated that women SMEs face significant barriers in digital literacy, online marketing, access to capital, and business networks. Interventions through locally based training and community mentoring resulted in a 63% increase in digital knowledge and participants' success in utilizing e-commerce platforms such as TikTok Shop and Shopee. Furthermore, this program encouraged the formation of community business networks, strengthened local product identity, and increased women's self-confidence and leadership. The program's impact extends beyond individual impacts to strengthening an inclusive and sustainable local economic ecosystem. These results confirm that a holistic, contextual, and participatory women's empowerment strategy is highly effective in driving SME-based socio-economic transformation.